Analysis and diagnosis of cracks in a single-family house in the city of Porto - PI (Research, Society and Development, 2022)
The growth of the civil construction sector in recent years has contributed to the increase in buildings in the country, mainly aimed at popular housing. With this, it has been observed that these are being built and designed on large scales and not having the necessary care during their execution, in such a way that in a short time damages will appear, which cause pathological manifestations of difficult correction or high cost. In this way, identifying, establishing preventive and corrective measures during the design, execution, material specification phases are important to prevent this type of anomalies. In order to contribute to the reduction of future problems, a case study was developed in a popular housing that presents fissures and cracks in various environments, in order to identify the origin of the pathological manifestations, as well as to present a diagnosis of the situation, seeking to understand the cause and consequence relationships, in order to present solutions and actions to regularize the problems encountered.